The Effective Factors on Employee Engagement and Healthcare Knowledge Management in the Organization: Meta-Analysis of Studies - Tahereh Abolghasem; Maryam Nakhoda; Sepideh Fahimifar; Mohammad Khandan (Tehran University of Medical Sciences, 2022)
Background and Aim: Knowledge management and employee engagement are the key factors for organizations to achieve competitive advantage, increase productivity and improve performance. The purpose of this study was to identify the relation of effective factors on employee engagement and healthcare knowledge management in the organization.  Materials and Methods: This research was applied in terms of systematic review and was done by meta-analysis-quantitative method. The statistical population included external research. Data collection tools are researcher-made checklist and EBL critical appraisal checklist (Glynn). For this purpose, comprehensive meta-analysis software version 2.0 was used.  Results: Findings showed that at 95% confidence level, employee engagement has a significant relation on healthcare knowledge management and was able to explain 37% of knowledge management. Leadership (0.349), Reward (0.616), Organizational Culture (0.655), Job Satisfaction (0.674), Innovation (0.493), productivity (0.411), organizational performance (0.775) and organizational learning (0.548) are factors that was affecting employee engagement and healthcare knowledge management. The results of heterogeneity tests showed that the studies were heterogeneous and therefore the random effect size was used. The funnel diagram shows high standard error and high bias. In other words, the distribution of research was not normal and random.  Conclusion: Managers can increase the level of engagement and management of organizational knowledge by focusing on the identified factors and its implementation in the organization and increase the level of desire and participation of employees in knowledge management processes.